Management of nitrogen fertilization in the succession black oat/corn in the no-tillage system - Mai, Marlon Evandro Müller; Ceretta, Carlos Alberto; Basso, Claudir José; Silveira, Marcio José da; Pavinato, Aurélio; Pavinato, Paulo Sérgio (Pesquisa Agropecuaria Brasileira, 2003)
The objectives of this study were to evaluate, in the succession black oat/corn, the dry matter production and N accumulation by black oat and their corn productivity, the influence of applied N on soil N content and the best application time of mineral N for corn production. The treatments were: 15-0-20-55, 30-0-20-40, 45-0-20-25, 0-35-20-35, 0-70-20-0, 0-0-20-70 and 0-0-0-0, corresponding, respectively, to the amounts of N (kg ha-1) applied at black oat tillering, before corn seeding, at corn seeding and corn sidedress. The increase in the dry matter production and of N accumulated in the black oat, with the applications of N in the black oat tillering, did not affect corn grain productivity. Although the application of N before corn seeding provided greater soil N content at the beginning of corn development, the application of N as sidedress provided the highest corn grain yield.
Keywords: grain; crop yield; dry matter; nitrogen; application date